OPTIMIZATION OF COLD STORAGE MAINTENANCE FOR ENHANCING ENERGY EFFICIENCY IN FISHERY PROCESSING: A CASE STUDY OF XYZ COMPANY - I Made Aditya Nugraha; I Ketut Sumandiarsa; I Gusti Ayu Budiadnyani; Pinky Natalia Samanta; Siluh Putu Sri Dia Utari; Ika Astiana; Iftachul Farida; Maria Delastrada Poy; I Gusti Made Ngurah Desnnajaya (Universitas Mataram, 2026)
The fisheries industry requires an effective cold chain system to maintain product quality and food safety, with cold storage functioning as a critical component in maintaining temperature stability prior to distribution. However, operational problems such as temperature fluctuations, equipment failure, and power outages frequently threaten cold storage performance and may lead to product deterioration and economic losses. This study aims to analyze cold storage maintenance management at XYZ Company and evaluate its effectiveness in supporting cold chain optimization. The research employed a qualitative descriptive approach conducted from October to March 2025 at XYZ Company, Sidoarjo. Data were collected through semi-structured interviews with 10 purposively selected respondents, direct observation, and analysis of maintenance records, SOPs, and temperature data logs. The results indicate that the implementation of scheduled preventive maintenance, IoT-based real-time monitoring, and automated control systems effectively maintained temperature stability within standard limits. These measures reduced the risk of protein denaturation, recrystallization, and microbial growth in fishery products. Energy efficiency improved through inverter technology and better insulation, while backup power systems and emergency SOPs minimize operational risks. In conclusion, optimized cold storage maintenance significantly enhances energy efficiency, operational reliability, and product quality, while supporting HACCP and ISO 22000 compliance and strengthening cold chain integrity in the fisheries processing industry.